Mixed Conducting Ceramic Membranes : Fundamentals, Materials and Applications - Zhu, Xuefeng; Yang, Weishen (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book is intended to bring together into a single book all aspects of mixed conducting ceramic membranes. It provides a comprehensive description of the fundamentals of mixed ionic-electronic conducting (MIEC) membranes from the basic theories and materials to fabrication and characterization technologies. It also covers the potential applications of MIEC membrane technology in industry. This book offers a valuable resource for all scientists and engineers involved in R&D on mixed conducting ceramic membrane technology, as well as other readers who are interested in catalysis in membrane reactor, solid state electrochemistry, solid oxide fuel cells, and related topics. Xuefeng Zhu, PhD, is a Professor at State Key Laboratory of Catalysis, Dalian Institute of Chemical Physics, Chinese Academy of Sciences, China. Weishen Yang, PhD, is the team leader for Membrane Catalysis and New Catalytic Materials and a DICP Chair Professor at State Key Laboratory of Catalysis, Dalian Institute of Chemical Physics, Chinese Academy of Sciences, China.
Keywords: Chemistry.; Energy storage.; Electrochemistry.; Chemical engineering.; elektronické knihy; electronic books